Construction of Mortality Tables using Bidirectional LSTM Neural Networks to Predict Death Probabilities - Nascimento, José Douglas (2022)
Mortality Tables are tables structured with mortality data, especially mortality rates observed at all ages, used in pension funds and life insurance markets. This article concerns the application of the neural network model to the construction of future mortality tables, using the Lee-Carter model for comparison. The proposed model was a LSTM (Long-Short Term Memory) Neural Network model, including a bidirectional variation. This network is characterized by the sequential processing of data over time. The data for the prediction came from historical mortality table data prepared by the IBGE (Brazilian Institute of Geography and Statistics) and the Human Mortality Database. The results point to a reasonable use as an auxiliary tool for predicting death probabilities.